Isolation and purification of elicitor molecules from Macrophomina phaseolina - P. VIDHYASEKARAN, A. RAMANATHAN and (Indian Phytopathology, 2002)
The isolation and purification of elicitor molecules from the cell wall and culture filtrate of M. phaseolina are described.